A survey of the young person's experience of Graves' disease and its management. (20th November 2020) - Lane, Laura Claire; Rankin, Judith; Cheetham, Tim
Abstract: Objective: A suboptimal quality of life (QoL) has been reported in patients with Graves' disease treated in adult life, but long‐term QoL in those treated in childhood and adolescence is unclear. We wanted to understand how Graves' disease and its management impact on the physical, psychological and social well‐being of young people and their longer‐term QoL. Design, patients and measurements: Two questionnaires were used to assess QoL and patient experience of Graves' disease; PedsQL™ Generic Core Scales and a Graves' disease questionnaire devised for this project. The anonymized questionnaires were sent to young people (<30 years) diagnosed with Graves' disease in childhood and adolescence and managed at a tertiary paediatric endocrine unit in the North of England. Respondent QoL scores were compared with a healthy UK cohort. Results: Questionnaires were sent to 51 young people, and 26 responded (51%). Graves' patients reported a lower total QoL score compared with the healthy cohort ( p  = .003). This was particularly apparent in the psychosocial domain ( p  = .0016). No patient regretted having definitive treatment (surgery/radioiodine), and all said they would recommend it to others. Half of those who had received definitive treatment still did not feel recovered. There was no difference in the long‐term QoL in those who did/did not receive definitive treatment ( p  = .40). Conclusions: This study highlights short‐ and long‐term impacts on the QoL and general well‐being of young people with Graves' disease. There were no regrets regarding the choice of definitive treatment. This information will help inform the counselling of patients and their families.